2006
DOI: 10.1007/s10661-006-9187-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of Geochemical Association of Some Trace Metals in the Sediments of Chilika Lake: A Multivariate Statistical Approach

Abstract: In order to establish the natural processes and geochemical factors responsible for enrichment of trace metal ions (Cu, Co, Ni, Zn and Cr) with respect to textural parameters (sand, silt and clay weight percentages) along with depth, multivariate statistical approach has been carried out for sediments in different water zones of Chilika lake, the largest brackish water lagoon in Asia. The rotated varimax factor results reveal that Cobalt enrichment is controlled by both textural parameters as well as adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…This study shows that concentration of Pb has decreased over the years, although the present concentration is still higher than the world rock average. Cobalt concentration is still high, particularly in Balugaon and Kaluparaghat, probably due to the impact of Balugaon township, thus corroborating with the finding of Panda et al 11 .…”
Section: Cationssupporting
confidence: 88%
See 2 more Smart Citations
“…This study shows that concentration of Pb has decreased over the years, although the present concentration is still higher than the world rock average. Cobalt concentration is still high, particularly in Balugaon and Kaluparaghat, probably due to the impact of Balugaon township, thus corroborating with the finding of Panda et al 11 .…”
Section: Cationssupporting
confidence: 88%
“…Unlike other coastal lagoons, the salinity of Chilika Lake fluctuates over a high range 11 resulting in variations in physical and chemical parameters of lagoon water.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Naming a few Bhattacharya et al, 1994;Panigrahy (2000); Chandramohan and Nayak,(1994) have enumerated the geology, geomorphology and tidal variation in the lagoon. Panda et al, (2006) have studied the distribution of trace metals in the surficial sediment, while Sahu and Adhikary, (1999) and Shaw et al, (2000) elucidated the distribution of seaweed and macrophytes, Panigrahy(1985); Panigrahi (2006Panigrahi ( ,2007Panigrahi ( ,2009) have described for phytoplankton and primary productivity potentiality of the lagoon where as Nayak et al, (2004) ;Panigrahi, (2009) and Mohapatra et al, (2007) studied the water chemistry and fishery production of the lake and the works of Zoological Survey of India regarding fauna of Chilika lake (ZSI 1995). Perusal of the literature has suggested that attention towards the study of macrobenthic organisms in the Chilika lake is still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…PCA with varimax rotation was performed with respected factor loadings were calculated using eigen values >1. The factor loadings may be classified as strong , moderate and week considering their significant influence in the geochemical processes corresponding to absolute loading values of > 0.70, 0.70 0.50 and 0.50 0.40, respectively (Liu et al, 2003;Panda et al, 2006). In the current study factor analysis separate the soil analysis data into three factors, which describe the distribution of elements in the studied soils.…”
Section: Rersults and Discussionmentioning
confidence: 99%